2017
DOI: 10.3389/fpls.2017.00559
|View full text |Cite
|
Sign up to set email alerts
|

The Major Qualitative Characteristics of Olive (Olea europaea L.) Cultivated in Southwest China

Abstract: Olive trees, originated from Mediterranean, have been cultivated in China for decades and show great adaption to local environment. However, research on this topic is limited. In this study, the major qualitative characteristics and changes of olive grown in southwest China were investigated. The results showed that oil accumulated during fruit development and reached its maximum value when fruit had fully ripened. Phenolic and flavonoid contents increase rapidly in the early growth stage (0–90 DAFB) and then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 32 publications
(46 reference statements)
4
12
0
2
Order By: Relevance
“…The gene expression pattern of OeDGAT1 in 'G' was consistent with a previous report of OeDGAT1 in 'Koroneiki' [67], presenting a typical normal curve, i.e., following maximal mRNA levels in September and then declining substantially. Although most TAGs in olive accumulated before they matured, it has been demonstrated that some oil cultivars, like 'A' in our study, have much shorter oil-filling periods than 'Koroneiki' and 'G' [68][69][70] (Figure S6). Olive oil is known for its high oleic acid content.…”
Section: The Expression Pattern Of Oebzip Was Related To Fruit Develomentioning
confidence: 60%
“…The gene expression pattern of OeDGAT1 in 'G' was consistent with a previous report of OeDGAT1 in 'Koroneiki' [67], presenting a typical normal curve, i.e., following maximal mRNA levels in September and then declining substantially. Although most TAGs in olive accumulated before they matured, it has been demonstrated that some oil cultivars, like 'A' in our study, have much shorter oil-filling periods than 'Koroneiki' and 'G' [68][69][70] (Figure S6). Olive oil is known for its high oleic acid content.…”
Section: The Expression Pattern Of Oebzip Was Related To Fruit Develomentioning
confidence: 60%
“…In contrast, higher amounts of luteolin-4'-O-glucoside were found and ranged from 17.21 to 74.32 mg/g DW between January and December, excluding April, with no significant differences detected during summer and autumn. These results may be explained by the embryonic development in April following the dormancy of the olive trees under the Liangshan climate [24] and likely linked to the increased activity of L-phenylalanine ammonia lyase (PAL) in the phenylpropanoid pathway [42]. Nevertheless, an opposite trend was observed in luteolin, which exhibited a persistent reduction during spring and winter, with the highest values detected in April (Table 2).…”
Section: Seasonal Variations In Oleuropein (Oe) and Flavonoid Composimentioning
confidence: 99%
“…Although Shiyan, Jintang, Wenxian, and Yongren have completed 40-50% of their total planned areas, they still have considerable potential for planting and development because of their large planned or growing area. Furthermore, Figure 8 In recent years, Chinese researchers have done some work about the quality, yield, and their relationship identification for the introduced varieties and locally bred varieties [21]. Olive mill wastewater (OMW) arises from the production of olive oil in olive mills.…”
Section: Development Potentialmentioning
confidence: 99%
“…According to the statistics of International Olive Council, China has an annual olive oil import of 30,000 to 40,000 tons, which far exceeds the import of table olives [28,29]. This is mainly because foreign In recent years, Chinese researchers have done some work about the quality, yield, and their relationship identification for the introduced varieties and locally bred varieties [21]. Olive mill wastewater (OMW) arises from the production of olive oil in olive mills.…”
Section: Development Potentialmentioning
confidence: 99%